Решить уравнение log7(x)+log49(36)=log1/7(2x+6)+log7(48)

DrZIP1st DrZIP1st    2   03.09.2019 14:30    3

Ответы
svv190204 svv190204  06.10.2020 14:57
Решение на фотографии
В 7-ой строчке не (х-3),а (х+3)
Решить уравнение log7(x)+log49(36)=log1/7(2x+6)+log7(48)
ПОКАЗАТЬ ОТВЕТЫ
MALsEeE1 MALsEeE1  06.10.2020 14:57
log7(x)+log49(36)=log1/7(2x+6)+log7(48)
log(1/a)x=-log(a)x
log(a^n)b^n=log(a)b
ОДЗ
{x>0
{2x+6>0⇒x>-3
x∈(0;∞)
log(7)x+log(7)6=-log(7)(2x+6)+log(7)48
log(7)x+log(7)(2x+6)=log(7)48-log(7)6
log(7)[x(2x+6)]=log(7)(48/6)
log(7)(2x²+6x)=log(7)8
2x²+6x=8
x²+3x-4=0
x1+x2=-3 U x1*x2=-4
x1=1 U x2=-4∉ОДЗ
ответ х=1
ПОКАЗАТЬ ОТВЕТЫ